Manuscripts 2001 Footwear Symposium in Zuerich / Switzerland (July 5-7, 2001) (2001)
Dr. Peter Cavanagh SHOES FOR THE DIABETIC FOOT: THE KEY ELEMENT IN PREVENTION Dr. Bernhard Segesser INJURIES AND SPORT SHOE DESIGN: WISH AND REALITY 1 - EE. Alcántara, J. C. Conzález, S. Alemany, A. C. García DEVELOPMENT OF A NEW METHOD TO MEASURE THE RECOVERY ABILITY OF INSOLE MATERIALS BY SIMULATING PLANTAR PRESSURES 2 - E. Alcántara, J. Solaz, J.C. González, A.C. García INFLUENCE OF RECOVERY ABILITY OF INSOLE MATERIALS IN HUMAN WALKING 3 - RE Arendse, MP Schwellnus, A St Clair-Gibson, TD Noakes, CL Vaughan DOES LOWER LIMB ALIGMENT DETERMINE THE KINEMATIC RESPONSE TO VARIATIONS IN BOUNDARY CONDITIONS? 4 - T. Asai and H. Murakami DEVELOPMENT AND EVALUATION OF A FINITE ELEMENT FOOT MODEL 5 - A. Bataller, E.Alcántara, J.C.Gonzalez, A.C. García. S. Alemany MORPHOLOGICAL GROUPING OF SPANISH FEET USING CLUSTERING TECHNIQUES 6 - A. Bataller, E.Alcántara, J.C.Gonzalez, A.C. García. S. Alemany INFLUENCE OF ANATOMICAL ELEMENTS IN THE FOOT PRESSURE DISTRIBUTION 7 - H. Baur, W. Bäurle, S. Grau, A. Hirschmüller, F. Mayer SELECTED PRESSURE DISTRIBUTION QUANTITIES OF HEALTHY RUNNERS AND RUNNERS WITH ACHILLES TENDINITIS WHILE RUNNING BAREFOOT AND SHOD 8 - D. Benoit, G. Cerulli, M. Lamontagne, C. Greaves, A. Caraffa, A. Liti, H. Schonuber. THE EFFECT OF REAR SPOILER RELEASE ON KNEE JOINT KINETICS DURING THE BACKWARD FALL IN SKIING 9 - J. Boo, S. Jung, D. Lee, S. Park, K. Jang THE STUDY ON PRESSURE DISTRIBUTION DURING WALKING OF THE KOREAN ELDERLY 10 - S.A. Bus, P.M.J. Kok, R.A.J. Wijlens BIOMECHANICAL INDICATIONS FOR SPECIFIC RUNNING SHOES FOR OLDER RUNNERS 11 - P. Carley, C. Favreau BIOMECHANICAL NYLON SKELETAL SOLE FOR FOOTWEAR REDUCES MUSCLE ACTIVITY 12 - V. R. Coyles, M. J. Lake and A. Lees DYNAMIC ANGULAR STIFFNESS OF THE KNEE AND ANKLE DURING BAREFOOT AND SHOD RUNNING 13 - S.J. Dixon, C.M. House and C. Waterworth THE INFLUENCE OF NEW AND DEGRADED INSOLES ON HEEL IMPACTS WHEN RUNNING IN MILITARY BOOTS 14 - A.M. Dowling and J.R. Steele WHAT ARE THE EFFECTS OF GENDER AND OBESITY ON FOOT STRUCTURE IN CHILDREN? 15 - E. Eils, M. Streyl, S. Linnenbecker, L. Thorwesten, K. Völker, D. Rosenbaum PLANTAR PRESSURE MEASUREMENTS IN A SOCCER SHOE: CHARACTERIZATION OF SOCCER SPECIFIC MOVEMENTS AND EFFECTS AFTER SIX WEEKS OF AGING 16 - E. Eils, C. Demming, G. Kollmeier, L. Thorwesten, K. Völker, D. Rosenbaum RESTRICTION OF MOTION DURING SIMULATED INVERSION ON A TILTING PLATFORM IN TEN DIFFERENT ANKLE BRACES 17 - V. Femery, P. Moretto, JM. Hespel, G. Lensel PLANTAR PRESSURE BIOFEEDBACK DEVICE FOR FOOT UNLOADING 18 - J. C. González, A. Bataller, E. Alcántara, A. C. García A COMPARISON OF FOOT-ORTHOSIS DIMENSIONS WITH AN ANTHROPOMETRICAL DATABASE OF CHILDRENS HEALTHY FEET 19 - J. C. González, E. Alcántara, A. Bataller, A. C. García PHYSIOLOGICAL AND SUBJECTIVE EVALUATION OF FOOTWEAR THERMAL RESPONSE OVER TIME 20 - F. Hagman, T. Ulicevic, A.A.F van de Ven, S.J.L. van Eijndhoven CALCULATING THE INVERSION/EVERSION MOTION OF THE FOOT FROM PRESSURE PLATE MEASUREMENTS 21 - E. M. Hennig GENDER DIFFERENCES FOR RUNNING IN ATHLETIC FOOTWEAR 22 - P. Hlavacek, M. Cernekova CHANGES TO THE INTERNAL SPACE OF WALKING SHOES AT GROUPS OF DIABETICS AND HEALTHY PEOPLE. 23 - Sukgill Jung, Sangdo Lee, Jinho Boo, Jaemin Park A CLASSIFICATION IN FOOT TYPE FOR DESIGNING FOOTWEAR OF THE KOREAN ELDERLY 24 - U.G. Kersting, G.-P. Brüggemann MECHANICAL STRESS IN CATERING PERSONNEL - LOWER EXTREMITY LOADING IN A WORK PLACE ENVIRONMENT 25 - C Kirtley AN INSTRUMENTED INSOLE FOR KINEMATIC AND KINETIC GAIT MEASUREMENTS 26 - F. Kleindienst, B. Krabbe, K. Westphal, M. Grandmontagne TEMPERATURE INFLUENCE OF VARYING MIDSOLE HARDNESS ON FUNCTIONAL PROPERTIES 27 - G.F. Kogler, M.R. Shorten PLANTAR PRESSURE DISTRIBUTION DURING GAIT IN A SUBJECT WITHOUT ADIPOSE TISSUE IN THE HEEL AND BALL OF THE FOOT. 28 - M. Kouchi, M. Mochimaru DEVELOPMENT OF A LOW COST FOOT-SCANNER FOR A CUSTOM SHOE MAKING SYSTEM 29 - JS. McCaw, B. Holubar, J. Hamill MISLEADING COMMENTS ABOUT SHOE MIDSOLE MATERIALS DO NOT AFFECT REARFOOT KINEMATICS DURING WALKING 30 - Erez Morag and Dan A. Johnson TRACTION REQUIREMENTS OF YOUNG SOCCER PLAYERS 31 - A. Mündermann, B.M. Nigg, D.J. Stefanyshyn, R.N. Humble A RELIABLE MEASURE TO ASSESS FOOTWEAR COMFORT 32 - M.A. Nurse, B.M. Nigg PLANTAR PRESSURE AND MUSCLE CHANGES WHILE WALKING IN DIFFERENT FOOTWEAR AND SENSORY CONDITIONS 33 - B. L. Patritti, M. J. Lake, N. J. Balmer and A. Lees. DISCRIMINATION OF LOWER LIMB IMPACT SEVERITY FOR TYPICAL LOADS EXPERIENCED DURING LOCOMOTION 34 - J. Pavlackova, P. Hlavacek PROPOSAL FOR A METHODOLOGY AND MEASUREMENT OF CHANGES TO THE INTERNAL SPACE OF CHILDRENS FOOTWEAR 35 - Kerry K. Rambarran, Marshall Kendall PLANTAR CENTER OF PRESSURE AND ITS EFFECT ON GOLF SWING DISTANCE AND ACCURACYPLANTAR CENTER OF PRESSURE AND ITíS EFFECT ON GOLF SWING DISTANCE AND ACCURACY 36 - D.J. Stefanyshyn, P. Stergiou, V.M.Y. Lun and W.H. Meeuwisse DYNAMIC VARIABLES AND INJURIES IN RUNNING 37 - Katsumasa Tanaka, Sadayuki Ujihashi, Makiko Morita, Katsushi Ishii CORRELATIONS BETWEEN THE MECHANICAL PROPERTIES OF RUNNING SHOES AND THE SENSORY EVALUATIONS BY DISTANCE RUNNERS IN RELATION TO THE WEAR OF OUTSOLE 38 - G.A. Valiant, B.J. Kilgore, J. Tawney, T.A. McMahon DEVELOPMENT OF A NEW RUNNING SHOE CUSHIONING TECHNOLOGY